Why-questions, topicality and intervention effects in Chinese - Jin, Dawei (Yearbook of the Poznan Linguistic Meeting, 2016)
This paper revisits intervention effects in Mandarin Chinese why-questions. I present new data showing that the ability for quantifiers to induce intervention hinges upon their monotonicity and their ability to be interpreted as topics. I then develop a semantic account that correlates topicality with monotone properties. Furthermore, I propose that why-questions in Chinese are idiosyncratic in that why directly merges at a high scope position that stays above a propositional argument. Combining the semantic idiosyncrasies of why-questions with the wide scope behaviors of topicality, I conclude that my account explains a wide range of intervention phenomena in terms of interpretation failure.